Patient safety and hospital accreditation : a model for ensuring success - Myers, Sharon (Springer Pub. Co., 2012)
Improving the culture of safety in our health care institutions is an essential component of preventing or reducing errors as well as improving overall health care quality. This book presents the clinically tested Myer's Patient Safety Model for health care system leaders, middle managers, and administrators to build their patient safety program and to help sustain, renew, or obtain accreditation.